2015
DOI: 10.1007/s10695-015-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hatching time on the bioenergetics of northern pike (Esox lucius) larvae from a single egg batch during the endogenous feeding period

Abstract: Size, caloric value and chemical composition were measured separately in the progeny of two northern pike (Esox lucius) females at 3-day intervals during the endogenous feeding period from hatching to final yolk resorption. Tissue, yolk and entire larvae were analysed separately in three groups of larvae that hatched at different times (between 88 and 106 degree-days post-fertilization). An integrated approach with the Gompertz model was used to compute the yolk conversion efficiency and time to maximum tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Very small females and those used reproductively for the first time demonstrate a tendency for producing a significantly smaller brood (Król and Zieliński 2015). That is why mixing of progenies with contrasted hatching times (with exception of fish at the same ontogenetic stage and homogenous in size) or progenies from females of different sizes, should be avoided -female size, egg size and size at hatching may be correlated (Wootton 1989;Baras and Jobling 2002;Steenfeldt et al 2011;Trabelsi et al 2013;Król and Zieliński 2015;Trabelsi et al 2016). Therefore, it is recommended to select proper sized females at the stage of spawn collection.…”
Section: Size-sortingmentioning
confidence: 99%
“…Very small females and those used reproductively for the first time demonstrate a tendency for producing a significantly smaller brood (Król and Zieliński 2015). That is why mixing of progenies with contrasted hatching times (with exception of fish at the same ontogenetic stage and homogenous in size) or progenies from females of different sizes, should be avoided -female size, egg size and size at hatching may be correlated (Wootton 1989;Baras and Jobling 2002;Steenfeldt et al 2011;Trabelsi et al 2013;Król and Zieliński 2015;Trabelsi et al 2016). Therefore, it is recommended to select proper sized females at the stage of spawn collection.…”
Section: Size-sortingmentioning
confidence: 99%
“…This difference could lead to a much higher energy value heterogeneity. Trabelsi et al (2016) showed within the same cohort a difference for biochemical and energy value (yolk sac and body) between early, middle and late hatching post-hatch stages. They found a better efficiency of yolk conversion in terms of energy for early and mid-hatched compared to the late hatched post-hatch stage.…”
Section: Hatchingmentioning
confidence: 78%
“…This phase would allow a smaller and perhaps less developed hatched fish to catch up with other individuals with an average size just prior to the onset of exogenous feeding (Kamler, 2008). This compensatory growth has already been observed for northern pike (Trabelsi et al, 2012(Trabelsi et al, , 2016 as well as other species such as Atlantic cod (Gadus morhua) (Jordaan et al, 2005) and common carp (Cyprinus carpio) (Korwin-Kossakowski, 2008). It is the result of an accelerated development for a very short period after hatching.…”
Section: Emergencementioning
confidence: 89%
“…Though few studies have quantified spatial variation in the quality of spawning and nursery habitat for freshwater fishes, the distribution of optimal nursery habitats is believed to be patchy (Roseman, Hayes, Taylor, Tyson, & Haas, 2005), and survival is highly dependent on spawning location (Höök, McCormick, Rutherford, Mason, & Carter, 2006) or passive transport to a suitable nursery area (Houde, 1969;Zhao, Jones, Shuter, & Roseman, 2009). Growth rates and survival of YOY fish have been linked to a plethora of environmental factors including water temperature (Hokanson & Koenst, 1986;Santucci & Wahl, 1993), hatch date (Trabelsi et al, 2016), prey availability (Roswell, Pothoven, & Hook, 2014), water level (Inskip, 1982), dissolved oxygen (Dombeck, Menzel, & Hinz, 1984), turbidity and availability of suitable aquatic vegetation (Casselman & Lewis, 1996). Therefore, selection of breeding and nursery areas can be conceptualised as a balancing of trade-offs to maximise growth and minimise mortality (e.g., Mumby et al, 2004;Rypel et al, 2012;Werner & Hall, 1988).…”
Section: Introductionmentioning
confidence: 99%